The conceptual foundations of investing : a short book of need-to-know essentials - Cornell, Bradford; Cornell, Shaun, 1979-; Cornell, Andrew, 1981- (John Wiley & Sons, Inc., 2018)
The need-to-know essentials of investing This book explains the conceptual foundations of investing to improve investor performance. There are a host of investment mistakes that can be avoided by such an understanding. One example involves the trade-off between risk and return. The trade-off seems to imply that if you bear more risk you will have higher long-run average returns. That conclusion is false. It is possible to bear a great deal of risk and get no benefit in terms of higher average return. Understanding the conceptual foundations of finance makes it clear why this is so and, thereby, helps an investor avoid bearing uncompensated risks. Another choice every investor has to make is between active versus passive investing. Making that choice wisely requires understanding the conceptual foundations of investing." Instructs investors willing to take the time to learn all of the concepts in layman's terms " Teaches concepts without overwhelming readers with math " Helps you strengthen your portfolio " Shows you the fundamental concepts of active investing The Conceptual Foundations of Investing is ultimately for investors looking to understand the science behind successful investing